2003
DOI: 10.1055/s-0037-1613595
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in venous disease

Abstract: SummaryQuality of life (QOL) can be defined as the functional effect of an illness and its consequent therapy upon a patient, as perceived by the patient. Studies on the impact of chronic venous disease on quality of life are scarce compared to quality of life research in other diseases. The purpose of this paper was to describe instruments that assess the quality of life in patients with chronic venous disease and to review the literature on this topic.A computer search of the MedLine database was performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Khan et al reported that DVT effect on QOL is noticeable years after the event 6. Van Korlaar et al noted that the decrease in QOL is related to symptom severity and development of PTS 7. In addition, Lubberts et al performed a large meta-analysis to assess health-related QOL in patients with DVT with at least one year of reported symptoms 8.…”
Section: Epidemiology Symptoms and Quality Of Life Of Patients With mentioning
confidence: 99%
“…Khan et al reported that DVT effect on QOL is noticeable years after the event 6. Van Korlaar et al noted that the decrease in QOL is related to symptom severity and development of PTS 7. In addition, Lubberts et al performed a large meta-analysis to assess health-related QOL in patients with DVT with at least one year of reported symptoms 8.…”
Section: Epidemiology Symptoms and Quality Of Life Of Patients With mentioning
confidence: 99%
“…The VEINES-QoL/Sym questionnaire specifically assesses quality of life and symptoms of a range of conditions in chronic venous disorders of the leg [10]. SF-36 is a generic QoL tool measuring health across three dimensions and including eight separate scales: functional status (physical functioning, social functioning, role limitations attributed to physical problems, and role limitations attributed to emotional problems), wellbeing (including mental health, energy and fatigue, and pain) and overall evaluation of health (including general health perception) [11]. Adverse events were also collected: major adverse events were defined as postoperative complications requiring admission or surgery and minor adverse events as postoperative complications requiring only medical treatment or monitoring (e.g., bruising, skin disorders, pain, puncture-site infection).…”
Section: Data Collectionmentioning
confidence: 99%
“…The VEINES-QoL/Sym questionnaire specifically assesses the quality of life and symptoms of a range of conditions in chronic venous disorders of the leg [10]. The SF-36 is a generic QoL tool measuring health across three dimensions and including eight separate scales: functional status (physical functioning, social functioning, role limitations attributed to physical problems, and role limitations attributed to emotional problems), wellbeing (including mental health, energy and fatigue, and pain) and overall evaluation of health (including general health perception) [11]. Adverse events were also collected: major adverse events were defined as postoperative complications requiring admission or surgery and minor adverse events as postoperative complications requiring only medical treatment or monitoring (e.g., bruising, skin disorders, pain, puncture-site infection).…”
Section: Data Collectionmentioning
confidence: 99%
“…A total of 32 GSV and 35 SSV were treated. The mean size (mm) of the treated veins was 8.5± 2.4 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Patients and Target Veinsmentioning
confidence: 99%